Influence of thermal stress on feed intake and body condition score during early postpartum period of crossbred cows in Kerala* - C. Ibraheem Kutty; C. P. Abdul Azeez; K. Promod; B. Bibin Becha; C. Sunanda; S. Lasna; K.S. Anil (Journal of Veterinary and Animal Sciences, 2020)
Increased milk production and environmental alterations caused by climate change makes dairy animals highly vulnerable to Thermal Stress (TS). Cross bred cattle shows some level of adaptation, characterized by reproductive performance of low level, almost uniformly throughout the year. Hence, objective of the present study was to find out the pattern of feed intake and body condition score of cross bred cows in the context of adaptation to TS across seasons prevailing in Kerala. The study was carried out at Livestock Research Station, Thiruvazhamkunnu, Kerala, in 22 post partum cows between Day 7 and Day 135 of calving. Daily intake of concentrate and weekly body condition score (BCS) were recorded. Blood samples were collected from 10 cows every week for estimation of thermal stress indicators and the climatic variables were recorded daily. Data were analyzed for monthly and seasonal variations and correlations between each other Temperature Humidity index (THI) and other climatic variables showed exposure of the animals to TS throughout the year. During summer months, ambient temperature and THI were significantly higher to cause moderate TS. Feed intake, BCS and cortisol levels were significantly high during summer, even though there was no significant correlation with climatic stress factors. HSP 70 was elevated throughout the year and significantly high during the period of moderate THI, indicating adaptation to TS. It is concluded that higher feed intake and BCS during summer months is attributable to TS adaptation because of continuous exposure across many years.